An analysis of the religious, social factors and income’s influence on the decision making in Islamic microfinance schemes - Shaheen, Mansori; Meysam, Safari; Zarina Mizam, Mohd Ismail (Emerald, 2020)
Purpose Islamic microfinance schemes are designed and developed with the primary intention of poverty alleviation and fulfillment of the Islamic law requirements. The purpose of this study is to investigate the effects of religiosity, religious leader’s endorsement, social influence and income on the intention to apply for Islamic microfinance among Muslims in Malaysia.